Metabolic phenotype of adult mice offspring obtained from different variants of embryo transfer - M. V. Anisimova; Ya. Gong; N. S. Yudin; Yu. M. Moshkin; L. A. Gerlinskaya (Вавиловский журнал генетики и селекции)
Assisted reproductive technologies (ART) increasingly occupy the study of human reproduction. In addition, in developed countries they contribute to breeding of more than 50 % of cattle. In the management of collections of genetic lines of laboratory animals, these technologies are obligatory components of cryopreservation and rederivation. ART procedures include the development of early embryos outside the mother’s body and the high probability of incomplete synchronization of the physiological state of the surrogate mother and transplanted embryos. Since all this occurs at the stage of the highest susceptibility of embryos to epigenetic reprogramming, the full cycle of ART and its individual components can lead to stable phenotypic changes in the offspring. Their reality is confirmed by studies of the morphological and functional characteristics of sexually mature offspring of CD1 outbred mice, obtained using different variants of early embryo transplantation. Comparative studies of body mass and body composition, basal glucose level and response to glucose load (glucose-tolerance test – GTT) have been done on sexually mature males and females. Animals were separated in 4 groups according to the variant of embryo transplantation: group (control) – natural mating; group (2cl-bl) – incubation of 2-cell up to blastocysts; group (2cl-2cl) – removal and transplantation of the 2-cell embryo without incubation; group (Bl-bl) removal and transplantation of the blastocysts without incubation. All embryos were transplanted to recipient females of the same line. It was found that sexually mature offspring obtained with all variants of transplantations had a higher relative fat content and, correspondingly, lower lean mass compared to the control. This effect was more pronounced in females than in males. Unlike body compositions, embryo transplantations had a greater effect on basal glucose concentration and GTT in males than in females. In this case, the offspring of the 2cl-2cl and 2cl-bl groups were characterized by a higher tolerance to glucose load (GTT) compared with the control and the Bl-bl group. Stable deviations of body compositions and glucose homeostasis indices detected in experimental groups of progenies indicate the phenotypic significance of the embryo transplantations per se.